The Development of Chinese Statistical Accounting During the Qin and Han Dynasties - M. A. Amurskaya (Учёт. Анализ. Аудит)
The Chinese experience in the development of accounting thought and economic statistics is of a particular interest to Russian scientific thought, since China has been confidently demonstrating economic success for many years. The research was carried out using the methods of sampling, grouping, systematization, comparison and generalization. The historical approach was applied to the analysis of theoretical and practical materials in the Chinese language. The two periods of the development of Chinese statistical thought are distinguished: 1) the period of the Qin dynasty (221-207 BC), starting from which the Chinese state is usually regarded as centralized, and statistical accounting is regarded as national; 2) the period of the Han dynasty (206 BC — 220 AD), during which the active development of statistical accounting continued and a fairly effective system was formed that satisfies all the needs of the state at the central and local level. The practical significance of the work lies in highlighting the methods of centralizing the collection of statistical data and the organization of statistics in China, the regulation of statistical accounting and related accounting. The article presents ideas and practical recommendations of the main thinkers, academicians and scientists (such as Sima Qian, Xu Gan) in the field of statistical accounting in China at that time.